Thermodynamic analysis of interaction of benzodiazepines and benzodiazepine receptors - Le Fei; Zhang Zhao-Geng; Zhou Ting-Chong (Acta Pharmacologica Sinica, 2016)
The characteristics of benzo-diazepines (BZ) binding to benzodiazepine receptors (BZ-R) of bovine cerebral cortex were investigated at 0-37 。C. The affinity of BZ binding to BZ-R decreased with the increase of temperatures, while the dissociation constant (Kd) determined by Scatchard analysis of saturation isotherm and the compititive inhibition increased with the increase of temperature. However. the maximal binding capacity (Bmax) did not vary with the temperature. Thermodynamic analysis indicated the reaction of BZ binding to BZ-R was spontaneous and of heat release. We find that the binding of antagonist yields an increase of entropy. but the agonist binding in a decrease of entropy. Antagonist binding to BZ-R is largely entropy-driven. while the binding of agonist. on the other hand. is associated with a decrease of enthalpy.